Donald Trump et la construction de l’éthos mis en scène en interaction : quand l’effet prime sur les faits - Anaïs Carrere (Corela)
This paper focuses on the construction of ethos of Donald Trump in the interview broadcasted in the U.S. on June 2st, 2024 on Fox News channel. This interview was given right after the former American President was convicted in The Stormy Daniels scandal on May 31st 2024. Both a quantitative and qualitative study examines how Donald Trump builds and promotes a valued ethos in and through his speech. The study of linguistic, rhetorical, stylistic, argumentative and interactional strategies that are analyzed as key features of Donald Trump's communicative style underline how Donald Trump attempts to convey a heroic image that might be accredited by a part of American citizens. The study also reveals that, in the backgrounds, lexicon, vocabulary or words are used to reach in discourse a strong emotional effect, based on negative emotions, such as fear, defiance, doubt, danger as means of (auto)promoting his heroic role when dealing with American diplomacy and with the Democrats when he was president from 2016 to 2020. Further, all these strategies give credit to the discourse and facilitate the manipulation of the co-speaker. Despite the verdict, the facts and the truth, Donald Trump seems to be “the best solution” for the United States.